Calcium fertilizers induce soil suppressiveness to Phytophthora cinnamomi root rot of Quercus ilex - Serrano, María Socorro; Vita, Paolo; Fernández-Rebollo, Pilar; Sánchez Hernández, María Esperanza (European Journal of Plant Pathology, 2011)
t Based on the observation that the root disease caused by P. cinnamomi on Q. ilex has a low incidence and severity in soils with medium-high Ca 2+ content, we studied the ability of Ca 2+ fertilizers to induce soil suppressiveness to the pathogen. Studies on cultures of P. cinnamomi exposed to different Ca 2+ fertilizers in vitro showed significant inhibition of sporangial, chlamydospore and zoospore production at millimolar concentrations while mycelial growth was mainly unaffected. Experiments performed with artificially infested soil showed that some Ca 2+ fertilizers induce a significant decrease on chlamydospore viability. Additionally, greenhouse experiments using artificially infested soils showed a significant reduction of foliar and root symptom severities in Holm oak seedlings growing in soils amended with Ca 2+ fertilizers. We suggest that limestone amendments in oak rangelands could enhance the suppressiveness of soils to P. cinnamomi, and it is likely that the inhibition of sporangial production was the main mechanism involved.
Keywords: fertilization; limestone; Oak decline; Rangelands